Privacy without Loss of Utility: Evaluation of De-identification Techniques in Deep Learning for Intensive Care Units - Rosa, Vitor Matheus Valandro da; Inocêncio, Giovana Nunes; Martina, Jean Everson (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21679, 2026)
The growing adoption of Deep Learning in Intensive Care Units depends on access to high-granularity clinical data, which conflicts with privacy regulations such as Brazil’s LGPD. This work evaluates the trade-off between de-identification techniques and clinical AI utility. Using the MIMIC-III database, we applied k-anonymity, l-diversity, and Differential Privacy to demographic attributes and trained the ConCare model for in-hospital mortality prediction. Re-identification risk was audited under Prosecutor, Journalist, and Marketer attack models. Results demonstrate that robust pseudonymization (k = 10, l = 2) reduces maximum risk from 100% to 1.09% without degrading predictive performance (AUROC 0.861 vs. 0.868 baseline). We conclude that preserving sample size is critical; Differential Privacy (ϵ = 2.0) discarded 16.3% of data, yielding inferior clinical utility (0.853) compared to syntactic approaches.